2012
DOI: 10.1007/s00114-012-0931-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential feeding deterrents found in hemlock woolly adelgid, Adelges tsugae

Abstract: The nonnative hemlock woolly adelgid (Adelges tsugae Annand, Hemiptera: Sternorrhyncha: Adelgidae) has been a significant mortality agent of eastern hemlock (Tsuga canadensis Carriere) throughout a large portion of its geographic range. During a study investigating adelgid vigor in relation to host health, it was noted that adelgid extracts ranged from a yellow to a deep red color. Analysis by GC-MS identified the presence of the anthraquinone, chrysophanol and its anthrone precursor, chrysarobin in the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Although the amount of increase in solar radiation after leaf senescence would vary considerably depending on the density of the hemlock canopy and surrounding deciduous trees, when leaf drop occurs, HWA begins producing wax which may protect it from the increased solar radiation. Jones et al [56] found that the HWA wax contains compounds that are predator deterrents. Although temperatures are much reduced during the fall, winter, and early spring compared to the summer, the production of wax may also reduce the effects of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of increase in solar radiation after leaf senescence would vary considerably depending on the density of the hemlock canopy and surrounding deciduous trees, when leaf drop occurs, HWA begins producing wax which may protect it from the increased solar radiation. Jones et al [56] found that the HWA wax contains compounds that are predator deterrents. Although temperatures are much reduced during the fall, winter, and early spring compared to the summer, the production of wax may also reduce the effects of solar radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor affecting the pest’s biological control is the production of a range of chemicals by certain life stages of HWA. These chemicals (anthraquinone, chrysophanol and its anthrone precursor, chrysarobin) may function as feeding deterrents against predators [118]. …”
Section: Potential Hwa Control and Management Optionsmentioning
confidence: 99%